Effect of Biochar and NPK Management on Growth and Yield of Moringa (Moringa oleifera) - Das, R K; Biswas, P K; Islam, M S; Roy, T S; Khan, M A (Bangladesh Agronomy Journal, 2025)
A field experiment was conducted at Ukhiya, Cox’s Bazar, Bangladesh, during 2022-2024 to evaluate the performance of Moringa oleifera var. PKM-2 under different bamboo biochar and NPK fertilizer treatments. The experiment was laid out in a randomized complete block design with three replications, consisting of four biochar doses (0, 5, 10, and 15 t ha−1) and four NPK fertilizer levels (0, 50, 100, and 150% of the recommended fertilizer dose, RFD), resulting in 16 treatment combinations. Results revealed that both biochar and NPK significantly improved plant growth and yield attributes. Application of 10-15 t ha−1 biochar enhanced plant height, crown spread, pod number, pod length and 1000-seed weight compared to the control. Fertilizer application at 100-150% RFD increased vegetative growth, pod development, and seed yield. Among the interactions, 10 t ha−1 biochar with 100% RFD produced the highest pod number (90 plant−1) and longest pods (55.69 cm), while 10 t ha−1 biochar with 150% RFD resulted in the tallest plants (3.95 m at 24 months). The heaviest seeds (140.54 g per 1000 grains) were recorded with 15 t ha−1 biochar. These findings suggest that 10 t ha−1 bamboo biochar combined with 100-150% RFD is optimal for maximizing moringa productivity under coastal agro-ecological conditions of Cox’s Bazar. Bangladesh Agron. J. 2024, 27(2): 108-115